2018
DOI: 10.3390/s18103409
|View full text |Cite
|
Sign up to set email alerts
|

StraightenUp+: Monitoring of Posture during Daily Activities for Older Persons Using Wearable Sensors

Abstract: Monitoring the posture of older persons using portable sensors while they carry out daily activities can facilitate the process of generating indicators with which to evaluate their health and quality of life. The majority of current research into such sensors focuses primarily on their functionality and accuracy, and minimal effort is dedicated to understanding the experience of older persons who interact with the devices. This study proposes a wearable device to identify the bodily postures of older persons,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…In [45], the monitoring of the posture of older persons using wearable sensors based on three inertial sensors was demonstrated. At the same time as they carried out daily activities, they generated indicators to assess their health and quality of life.…”
Section: Sensors In Healthcare Home Medical Assistance and Continuomentioning
confidence: 99%
“…In [45], the monitoring of the posture of older persons using wearable sensors based on three inertial sensors was demonstrated. At the same time as they carried out daily activities, they generated indicators to assess their health and quality of life.…”
Section: Sensors In Healthcare Home Medical Assistance and Continuomentioning
confidence: 99%
“…The first main category gathers articles that intend to test a new activity classification method by developing an algorithm and/or a measurement device specific to their work [ 60 , 61 ]. Authors of these studies set up algorithms that allow, from previous annotated observations of participants performing activities (labeled training data), to determine which type of activity is performed during an analysis of a signal section (see Section 5 for more details on machine learning procedures for activity classification).…”
Section: Aims Of the Studiesmentioning
confidence: 99%
“…Of all studies using more than one sensor, 67% use four or less sensors. [ 27 , 28 , 54 , 61 , 65 , 74 , 86 ]). Moreover, only three studies use more than ten IMUs—these studies use the IGS-180 suit consisting of seventeen IMUs [ 18 , 63 , 70 ].…”
Section: Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent literature review identified that the most commonly used technologies in cardiovascular disease monitoring are mobile apps, and that these applications are mostly used for blood pressure monitoring, cardiac rehabilitation, arrhythmia monitoring, medication management and social support [14]. Recently, several mobile health technologies (mHealth) have emerged with the aim of providing innovative and efficient ways to help older adults in their daily lives and to reduce the cost of health care [15,16], e.g., monitoring vital functions and disease patterns [17], detecting falls or changes in motion patterns or routines [18,19] or informing health care professionals of patients' health status [20]. Digital health information can be used to evaluate health anomalies and for early detection of certain chronic diseases such as Parkinson's or spinal pain [21].…”
Section: Introductionmentioning
confidence: 99%